O mercado segurador brasileiro de 1985-2007: estrutura do setor e estratégias de negócios da Bradesco Seguros S.A. e Sul América S.A. - Silva, Andressa Leite da (Universidade do Vale do Rio do Sinos, 2008)
The insurance sector in Brazil has had significant changes since the open market of the Brazilian economy. This research has as its objectives to analyze how Bradesco Seguros S.A. and Sul América S.A. reorganized themselves and redefine their business strategies, from 1985 to 2007, due to the relevant changes occurred in the Brazilian insurance market. From an exploratory study, using secondary source of information, it was generated explanations to answer the questions defined as objectives of this research. After the conclusion of this study, it was possible to verify that the groups formation, resulted, mainly, from its strategic decisions, and do not as a way of re-appropriation to the changes that happened in its business atmosphere, that altered the structure of the Brazil’s insurance sector. However, it is believed that the groups took the advantage of the stimulus that came from the economic environment. As for the strategic decisions of the groups, in the auto field, it has been concluded that the st
Keywords: estratégia de negócios; seguro de automóvel; setor de seguros; business strategy; car insurance; insurance sector; Ciências Sociais Aplicadas